PUBLIC FINANCIAL MANAGEMENT PRACTICES AND PERFORMANCE OF SELECTED COUNTY GOVERNMENTS IN KENYA - Mong’are, Winnie; Atheru, Gerald (American International Journal of Social Science Research, 2023)
Although county governments were introduced for devolution, misappropriation and corruption hinder this objective. This study aimed to examine how financial management practices affect the performance of Central Rift County governments. The research was informed by agency, institutional, and stewardship theories. A descriptive research design was used. The target population was employees within Nakuru County’s public finance sector. A census of all 80 employees was done, and a Cronbach alpha of 0.7 was used to determine the reliability of the research instruments. Secondary data was collected from published materials from county and government agencies. Data was analyzed through the statistical package for social sciences to provide inferential and descriptive statistics. The study revealed that county governments use budget implementation, regular reviews, and monitoring to improve compliance and performance. There was a moderate positive and statistically significant correlation between public budgeting on the performance of Central Rift County governments (r = 0.443; p < 0.05); an average positive and statistically significant correlation between public financial reporting on the performance of Central Rift County governments (r = 0.441; p < 0.05); a moderate positive correlation between public revenue mobilizations on the performance of Central Rift County governments (r = 0.441; p < 0.05), and a moderate positive correlation between public finance procurement on the performance of central rift county governments (r = 0.441; p < 0.05). There is a need to realign the budget processing and reporting format in conformity with IPSAS reporting standards.JEL Classification Codes: H1, H2, H3, H6, H6.